Ejecución obligatoria de los ejes de tratamiento de las personas privadas de la libertad para acceder a los beneficios carcelarios. - Macas Criollo, Alex Jonael (2023)
The title of this Integrative Curriculum Work is: "Mandatory Implementation of the Treatment Axes for People who are Deprived of Liberty to Access Prison Benefits." The interest in developing this research topic stems from the lack of operability of the treatment axes due to the deficiencies in the National Social Rehabilitation System, which have highlighted its weakness in the rehabilitation of incarcerated individuals within prisons. The study demonstrates the lack of effectiveness of the treatment axes, as the Penitentiary System lacks suitable infrastructure to facilitate the normal implementation of plans and programs that enable incarcerated individuals to rehabilitate and reintegrate into society. Additionally, Article 9 of the Organic Penal Law Code establishes that the participation of incarcerated individuals in the treatment is voluntary and individual, leading to disinterest and apathy among them. Therefore, mandatory implementation must be ensured prior to obtaining penitentiary benefits. Furthermore, the Government has not allocated sufficient budget to achieve the goals of the National Social Rehabilitation System through the creation of efficient public policies. Consequently, this research aims to identify the causes preventing Rehabilitation Centers from fulfilling their intended purpose. In this Integrative Curriculum Work, resources, materials, and methods were applied to facilitate the research. Interviews and surveys were conducted with legal professionals specialized in the law field. The results of these interviews and surveys served as the basis for this work, with the goal of determining whether the mandatory implementation of treatment axes for incarcerated individuals can guarantee mere rehabilitation and social reintegration in this vulnerable group. The study also aims to provide suggestions to change the current reality of the penitentiary system and establish proactive guidelines that will greatly contribute to supporting this work and serve as its foundation.